Vision 2050: Reaction Engineering Roadmap - Bollini, Praveen; Diwan, Moiz; Gautam, Pankaj; Hartman, Ryan L.; Hickman, Daniel A.; Johnson, Martin; Kawase, Motoaki; Neurock, Matthew; Patience, Gregory S.; Stottlemyer, Alan; Vlachos, Dionisios G.; Wilhite, Benjamin (ACS Engineering Au, 2023)
This perspective provides the collective opinions of a dozen chemical reaction engineers from academia and industry. In this sequel to the “Vision 2020: Reaction Engineering Roadmap,” published in 2001, we provide our opinions about the field of reaction engineering by addressing the current situation, identifying barriers to progress, and recommending research directions in the context of four industry sectors (basic chemicals, specialty chemicals, pharmaceuticals, and polymers) and five technology areas (reactor system selection, design and scale-up, chemical mechanism development and property estimation, catalysis, nonstandard reactor types, and electrochemical systems). Our collective input in this report includes numerous recommendations regarding research needs in the field of reaction engineering in the coming decades, including guidance for prioritizing efforts in workforce development, measurement science, and computational methods. We see important roles for reaction engineers in the plastics circularity challenge, decarbonization of processes, electrification of chemical reactors, conversion of batch processes to continuous processes, and development of intensified, dynamic reaction processes.